The southern home of yhwh and pre-priestly patriarchal/exodus traditions from a southern perspective - Tebes, Juan Manuel (2018)
Fil: Tebes, Juan Manuel. Pontificia Universidad Católica Argentina. Facultad de Ciencias Sociales. Instituto de Investigaciones de la Facultad de Ciencias Sociales; Argentina